Consumer Challenges of the Socio-Economically Disadvantaged in South Africa and the Role of Consumer Legislation - Lindeka Tentu; Karunanidhi Reddy (African Journal of Inter-Multidisciplinary Studies)
In South Africa, high poverty and low literacy rates significantly affect the consumer market, especially for vulnerable individuals in disadvantaged communities. These consumers encounter difficulties when dealing with suppliers, including purchasing inferior quality goods, facing higher prices, and needing to make multiple trips to stores. This disparity is pronounced within the market, which encompasses literate ordinary consumers and vulnerable individuals with low literacy levels or illiteracy. Due to their socio-economic challenges, these vulnerable consumers often tolerate unethical business practices and find it challenging to access legal support. Through a quantitative survey, this article explores consumer challenges faced by socio-economically disadvantaged individuals in Illovo Township, Bhekulwandle, KwaZulu-Natal, South Africa. The study is grounded in the Consumer Justice Theory, and advocates for equitable treatment and protection of historically disadvantaged consumers under relevant consumer protection legislation. The findings reveal that socio-economically disadvantaged consumers face challenges with complex contracts, lack of legal recourse due to financial constraints, and lengthy cancellation processes, leading to acceptance of poor service. Awareness of consumer rights remains low among respondents. However, the article concludes that the government, suppliers, and consumer bodies bear a significant responsibility to ensure equal protection for all consumers, particularly those from disadvantaged backgrounds.